Monitoring the development of young camels and wool quality camels of Kazakhstan population. Issue 1 (November 2020) - Alibayev, N; Semenov, V; Baimukanov, A; Ermakhanov, M; Abuov, G
Abstract: The purpose of the study is to explore economically valuable signs of female camels and set the selection criteria for down hair fibers according to length and fineness. The shorn wool amount was determined during spring shearing by individual weighing of wool with 0.1 kg precision balance. Selection criteria for down hair in Arvana breed are elaborated, with the parameters of length min. 9 cm and fineness of 15-19 microns, and for Kazakh Bactrian breed – with the parameters of length min. 12 cm and fineness of 14-18 microns; these criteria were used to select and form preferable types of 54 and 224 animal units correspondingly for further selection process works to increase wool production in stocks. For Bactrian camels, these parameters are 11.0% lower in Kospak-1 camels, 12.2% lower in Kospak-2 camels and 4.8% lower in Kospak-3 camels. As for the length of down hair fibers, it is almost the same for all the studied young camels. The absolute gain of the body weight of colts of domestic breeds is relatively high, making 103.8-127.4 kg, with the relative gain of 329.5-397.8 kg and with the average daily gain – 576.7-707.8 g.